Moderation analysis exploring associations between age and mucocutaneous activity in Behcet's syndrome: A multicenter study from Turkey - AKSOY, AYSUN; ALİBAZ ÖNER, FATMA; MUMCU, GONCA; İNANÇ, GÜZİDE NEVSUN; DİRESKENELİ, RAFİ HANER; ERGUN, SAFİYE ATLAS TÜLİN (WILEY, 2020)
The aim of the present study was to examine the effects of age on mucocutaneous activity by using moderation analysis in Behcet's syndrome (BS). In this cross-sectional study, 887 BS patients (female : male, 481:406; mean age, 38.4 +/- 10.9 years) followed in 13 tertiary centers in Turkey were included. Mucocutaneous activity was evaluated by using the Mucocutaneous Index (MI) according to sex and disease course. Moderation analysis was performed to test the effect of age on mucocutaneous activity. A moderator variable is a third variable and affects the relationship between independent and outcome variables. Age was chosen as a potential moderator variable (interaction effect), MI score as the outcome variable and sex as an independent variable in the analysis. The moderation analysis tested the effects of age in three steps: whole BS patient group, patients without systemic involvement and those with systemic involvement. The moderation model was only significant in BS patients with systemic involvement (P = 0.0351), and a significant relationship was observed between female sex and MI score (P = 0.0156). In addition, the interaction plot showed that female patients had increased MI scores compared with male patients, especially in the 28-year-old age group (P = 0.0067). Moreover, major organ involvement was newly diagnosed in the majority of these young female BS patients. Our results suggest that the relationship between sex and mucocutaneous activity was moderated by age in the systemic involvement group. Also, increased mucocutaneous activity may be associated with new major organ involvement in young female BS patients with systemic involvement.
Keywords: Behcet's syndrome; moderation analysis; mucocutaneous activity; Mucocutaneous Index; sex; ORAL ULCER ACTIVITY; QUALITY-OF-LIFE; DISEASE-ACTIVITY; OUTCOME MEASURES; COMPOSITE INDEX; MANIFESTATIONS; INVOLVEMENT; SEVERITY; MEDIATOR; HEALTH